Costs incurred by the mother as a result of childbirth and upbringing − changes in the career path - Jędrzychowska, Anna; Poprawska, Ewa (Koszty poniesione przez matkę w wyniku urodzenia i wychowania dziecka − zmiany w ścieżce kariery zawodowej, 2020)
The article is a part of research on the financial consequences of household members’ loss of health and life, in this case − a child. The amount of this loss can be estimated using, among others, the cost approach, including expenses and lost benefits associated with raising a child. The article analyzes lost benefits – the financial consequences that the mother incurs mainly due to birth and childcare, and which are associated with changes in career development. Calculations are presented for selected scenarios for the career path and a model for assessing the income gap between women: mother and a childless one has been proposed. It should be remembered that the child appears most often at the beginning of the mother’s professional career. This is the time of the fastest wage increase. Therefore, given the non-linear trend of wage increases with seniority (close to exponential), the ‘severity’ of the child’s appearance in the initial period of work is significant
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 66-75
Keywords: motherhood gap; personal injury; insurance; luka dochodowa; szkody osobowe; ubezpieczenia